Potret kesadaran ekologis masyarakat: Studi pengetahuan masyarakat tentang limbah air rumah tangga terhadap pencemaran lingkungan - Rismawati, Ananda; Sya’aban, Moh B Ali (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2023)
Environmental pollution is a major problem in the development of science. The problem of water pollution is one of the consequences and impacts of the development of science itself. The discussion of this article uses descriptive research with a field observation approach and interviews with 60 respondents in the Tomang Village, West Jakarta. The purpose of this study was to determine the ecological awareness of the community through the knowledge and attitudes of the community regarding household water waste which is one of the results of environmental pollution in the Tomang Village area. Community knowledge and attitudes towards household waste are needed as the first step to prevent environmental pollution, especially water pollution in waterways and rivers that have the potential to contaminate groundwater in the vicinity. Based on the results of the study it was found that some people did not understand what household waste was and its impact on health and the surrounding environment, the use of detergents, soaps, shampoos and oil in their daily activities was carried out more than once a day. Some people who do not have a septic tank dispose of household wastewater directly into the nearest river or river. Efforts that can be made by the government are socialization and training regarding household waste water and its processing which is very necessary for public knowledge so that they are not negligent in the use of materials that will pollute the environment and are more aware in protecting the environment. In addition, a septic tank development program is needed for people who do not have one, as well as the construction of infiltration wells to collect rainwater that can be used for daily activities.